IN VITRO ANTHELMINTIC ACTIVITY OF SYZYGIUM AROMATICUM FLORAL BUDS AND CINNAMOMUM ZEYLANICUM BARK AQUEOUS EXTRACTS - P. LAKSHMI KUMARI; A. SUJITHA; N. MAHAMMAD RAFI (International Journal of Pharma and Bio Sciences, 2015)
Cloves (Syzygium aromaticum) are the aromatic dried flower buds of a tree in the Myrtaceae family and Cinnamon (Cinnamomum zeylanicum) bark are common Indian spices with enormous medicinal value. This study investigates in vitro anthelmintic activity of aqueous extracts of S. aromaticum (floral buds) and C. zeylanicum (bark). Phytochemical analysis of the extracts of S. aromaticum and C. zeylanicum revealed the presence of alkaloids, tannins, phenolics, phlobatannins, cardiac glycosides, anthraquinone glycosides, hydroxyl anthraquinones, flavonoids and terpenoids. Aqueous extracts of S. aromaticum and C.zeylanicum were evaluated for anthelmintic activity against Indian earthworm Pheritima posthuma. Albendazole (10 and 20 mg/ml) was used as a reference standard. Various concentrations (5, 10 and 20 mg/ml) of both plant extracts were tested and results were expressed in terms of time taken for paralysis (PT) and death (D) of worms. The potency of the above extracts was found to be inversely proportional to PT and D. Dose dependent activity was observed in the plant extracts. At higher dose of 20 mg/ml C. zeylanicum showed significant activity as compared to S. aromaticum.